METODE DAKWAH BI AL-KITABAH DATO’ HAJI SYEIKH MUHAMMAD FUAD BIN KAMALUDIN AL-MALIKI - Zikmal Fuad (Hikmah, 2018)
Dato 'Haji Syeikh Muhammad Fuad Bin Kamaludin al-Maliki among the da'wah leaders in Malaysia. Many of those who do not know his character. He is a productive writer who strives to continue to understand the community about Islam. This article aims to examine the method of dakwah bi al-kitabah Sheikh Muhammad Fuad in delivering dakwah to the Muslim community. The study also aims to study the contributions of Syeikh Muhammad Fuad through his writings. The research methodology used in this research involved literature and field studies. The literature study uses content analysis and document analysis, while field research uses observation and interview methods with respondents of various groups and backgrounds. Among the findings of Sheikh Muim's study was a respected scholar, preacher, author and debater. The study also found that was a da'wah leader who left a legacy of knowledge and thought.Keywords: Sheikh, character, Da'wah, al-Kitabah, Society